Perfil de comercialização das Anonáceas nas Ceasas brasileiras - Watanabe, Hélio Satoshi; Oliveira, Sabrina Leite De; Camara, Fabiane Mendes Da; Almeida, Gabriel Vicente Bitencourt De [UNESP]; Alves, André Afonso (Sociedade Brasileira de Fruticultura, 2014)
The anonas' quantity at Brazilian main terminal markets is growing and is concentrated at CEAGESP - 61%. SIEM's data has shown a large supply growth of atemoya and soursop, 35% and 32% respectively, and a sweetsop's decrease - 20%, from 2011 to 2012 at CEAGESP. Atemoya (54%), soursop (41%) and sweetsop (5%) are the most important anonnas at CEAGESP terminal market. The origin is concentrated in the state of Bahia - soursop and sweetsop and atemoya from Minas Gerais and São Paulo. The study of the value differentiation causes, comparing atemoya batches of the same grade size, of maximum and minimum value, at the same day, has shown the size homogeneity as the most important characteristic for value differentiation. The best strategy to promote the value differentiation for the grower is to improve size selection - its visual homogeneity.

A quantidade de anonáceas comercializadas nas principais centrais de abastecimento está crescendo e concentrada na CEAGESP - 61%. As informações coletadas pelo SIEM da CEAGESP mostram, entre 2011 e 2012, o grande crescimento da oferta de atemoia e de graviola, respectivamente, 35% e 32%, entre 2011 e 2012, e a queda do volume de pinha - 20%, entre 2011 e 2012. A atemoia (54%), a pinha (41%) e a graviola (5%) são as anonáceas mais importantes comercializadas na CEAGESP. A origem é concentrada nos Estados da Bahia - pinha e graviola, e em Minas Gerais e São Paulo - atemoia. O estudo das causas da diferenciação de valor, entre lotes de atemoia de valores máximo e mínimo, de mesma classificação de tamanho, no mesmo dia, mostrou que a homogeneidade visual de tamanho é a maior responsável pela diferenciação de valor. A melhoria da seleção por tamanho é a melhor estratégia de diferenciação de valor a ser adotada pelo produtor.
Annona's marketing profile at brazilian terminal markets
Keywords: valor; CEAGESP; graviola; pinha; atemoia; CEAGESP; soursop; sugar apple or sweetsop; atemoya; quality